2021
DOI: 10.1101/2021.11.26.470138
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Noise in a metabolic pathway leads to persister formation in Mycobacterium tuberculosis

Abstract: Tuberculosis is difficult to treat due to dormant cells in hypoxic granulomas, and stochastically-formed persisters tolerant of antibiotics. Bactericidal antibiotics kill by corrupting their energy-dependent targets. We reasoned that noise in the expression of an energy-generating component will produce rare persister cells. In sorted low ATP M. tuberculosis grown on acetate there is considerable cell-to-cell variation in the level of mRNA coding for AckA, the acetate kinase. Quenching the noise by overexpress… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…In Mycobacteria, the stress response pathway involving the σ factor SigE is characterized by a bimodal expression of the stringent response modulator Rel, resulting in a subpopulation with a high Rel translation (H-state) [174,175], and since SigE has also been implicated in persister formation [176], the H-state might represent persistence, although this speculation has not been validated. Additionally, it was recently reported that stochasticity associated with acetate kinase essential for acetate to enter the Krebs cycle mediates persistence in M. tuberculosis [177]. In Bacillus subtillis, the noise-driven ComKS system regulates competence and growth arrest, imposing a triggered persistence [178].…”
Section: Is Persister Formation Stochastic Deterministic or Both?mentioning
confidence: 99%
“…In Mycobacteria, the stress response pathway involving the σ factor SigE is characterized by a bimodal expression of the stringent response modulator Rel, resulting in a subpopulation with a high Rel translation (H-state) [174,175], and since SigE has also been implicated in persister formation [176], the H-state might represent persistence, although this speculation has not been validated. Additionally, it was recently reported that stochasticity associated with acetate kinase essential for acetate to enter the Krebs cycle mediates persistence in M. tuberculosis [177]. In Bacillus subtillis, the noise-driven ComKS system regulates competence and growth arrest, imposing a triggered persistence [178].…”
Section: Is Persister Formation Stochastic Deterministic or Both?mentioning
confidence: 99%